Efforts Of Islamic Boarding School Management To Improve The Life Skills Of Students At The Raudlatul Ulum 1 Putri Islamic Boarding School - Kurnia, Fitri Ayu; Abdulloh, Abdulloh (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Islamic boarding schools (pondok pesantren) are regarded as vital educational institutions that play an important role in the progress and development of education. Additionally, they are considered alternative solutions for various educational challenges. This educational model, which focuses on religious studies, particularly Islam, has become a model and the precursor for the current educational system in Indonesia. Implementing life skills education within these institutions produces highly competitive students. With life skills training, they become more productive and capable of competing in the job market. The research questions are: (1) What efforts do the administrators of Pondok Pesantren make to enhance students' life skills? (2) What are the outcomes of these efforts? The objectives are: (1) To identify the efforts made by Pondok Pesantren administrators to enhance the life skills of students, and (2) To determine the results of these efforts. The findings indicate that instilling educational values in Islamic boarding schools through muhadhoroh (speeches) and extracurricular activities have a positive impact. The strategies used to instill Islamic educational values through muhadhoroh and extracurricular activities have proven effective. Keywords: Islamic boarding schools, Life skills, Religious education